Suitability of Metastatic Lung Tumors for Stereotactic Body Radiotherapy. (21st April 2022) - Eriguchi, Takahisa; Tsukamoto, Nobuhiro; Kumabe, Atsuhiro; Ogata, Takeru; Inoue, Yoshimasa; Sugawara, Akitomo
Abstract: We investigated factors influencing local control of lung metastases treated with stereotactic body radiotherapy (SBRT) and determined the type of lesions for which SBRT is more suitable. Ninety-six patients and 196 tumors were included. Median follow-up duration was 32.0 months (range 4.7–95.8). The two-year local recurrence rate was 15.2% (95% confidence interval: 10.2–21.3). Multivariate analysis revealed biological effective dose, ultracentral tumor location, reirradiation, and prior chemotherapy as significant factors. SBRT is suitable for lung metastases, especially for peripheral tumors and those located in the inner lung parenchyma. For ultracentral lesions and recurrent lesions after SBRT, metastasectomy is recommended.